The impact of teaching interventions in education for sustainable development: An experimental case study - Johannes Joost Platje; Aniela Styś; Markus Will; Wim Lambrechts (The Central European Review of Economics and Management (CEREM), 2022)
Aim: Questionnaire research can be used as a teaching instrument and to measure the impacts of education for sustainable development. This paper presents a case study of a teaching intervention regarding students' perception of operations and (supply) management fragilities, such as dependency on few customers or suppliers; difficult to find employees; and low probability, high impact events for business sustainability. The teaching intervention focused on side effects of innovations, leading to vulnerabilities that can threaten the existence of an enterprise. This research was carried out in the context of the capacity for creating an Early Warning System for small probability, high impact events. The following issues are addressed in the paper: 1). The impact of the teaching intervention on students' perceptions; 2). Differences in perception between non-attending (N = 128) and attending students (pre-test N = 139; post-test N = 119). Design / Research methods: This paper discusses whether teaching interventions can influence the awareness of fragility issues as well as low probability, high impact events. The case-study is based on an experiment in a marketing course for management students of a large private business school in Wroc±aw (Poland) in April-May 2019. Before start of classes students filled out a questionnaire (Attending Students). A teaching intervention slide was used in every lecture. At the end of the course, all students (also the students absent during the first classes) filled out the repeat questionnaire. Statistical analysis was carried out whether there were differences between Attending Students filling out both questionnaires, and students only filling out the repeat questionnaire (Non Attending Students). Conclusions / findings: The findings show that students struggle to grasp the complexities and uncertainties surrounding sustainability and fragility issues in relation to the business context. The teaching interventions had limited impact on the ability of students to engage in these issues, albeit significant differences between attending and non-attending students were observed. A limitation of the results is that this study only concerned a case study of a specific group of students. An implication requiring deeper research is that while teachers can do in-depth exercises and provide lectures, a part of the students, being less motivated to obtain knowledge, is unlikely to grasp sustainability issues, when not included in assignments, examination preparation, or compulsory rather than elective courses.
Keywords: I21; O31; Q01; 330; education for sustainable development; fragilities; Black Swans; innovation for sustainable development